Identification and Characterization of Dimorphic Expression of Sex-Related Genes in Rock Bream, a Fish With Multiple Sex Chromosomes - Li, Huan; Zhu, Qihui; Chen, Ruiyi; Liu, Mingtao; Xu, Dongdong (Frontiers in Genetics, 2021)
The rock bream (Oplegnathus fasciatus) is a typical fish with a unique multiple sex chromosome system. In this study, we investigated the gonads and brains of both males and females using RNA-Seq to identify sex-related genes and pathways. In accordance with the dimorphic expression profiles, combined with GO and KEGG enrichment analyses, several potential genes and pathways associated with sex determination were obtained from transcriptional analysis, especially some sex-biased genes and pathways. Next, we selected 18 candidate genes and analyzed their expression in different tissues and developmental stages. We found that the expression levels of Amh, Dmrt1, Sox9, Dmrtb1, and Nanos2 were significantly higher in the testis than those in the ovary or other tissues, whereas the expression levels of ZP4, Bouncer, RNF208, FoxH1, and TOB were significantly higher in the ovary than those in the testis. Furthermore, the expression levels of these genes in different developmental stages of gonads also showed sexually dimorphic patterns, suggesting that they might play important roles during gonadal development. These genes are useful markers for investigating sex determination and differentiation in rock bream. The findings of this study can provide insights into the molecular mechanisms of sex determination and differentiation in fish with multiple sex chromosome systems.